Effects of Outsourcing on Employment Generation: Evidence from the Telecommunications Sector of Uganda - Nalubega, T.; Kasumba, D.C.; Uwizeyimana, D.E. (Journal of Reviews on Global Economics, 2019)
Outsourcing has emerged as a globally embraced business strategy that involves restructuring geared at improving flexibility, inducing innovation and creativity, whilst simultaneously creating greater employment opportunities. Telecommunications companies worldwide have adopted outsourcing strategies leaving them to concentrate on their core business. In Uganda almost all telecommunications companies have also followed the outsourcing trend. However, despite the increasing adoption of outsourcing strategies, there is a dearth of literature about how outsourcing in the telecommunications sector has contributed to the generation of employment in Uganda. MTN Uganda and Airtel Uganda were selected as study sites and a mixed-methods approach was followed for the data collection and analysis. The quantitative data was analysed through descriptive statistics and inferential analysis using version 23 of the statistical package for social sciences (SPSS). The descriptive statistics were analysed, confirming that a multitude of business functions are being outsourced to other companies in Uganda. Correlation analyses were performed for purposes of generating inferential statistics and the findings revealed that the outsourcing of Human Resource Management (HRM) functions, Information Technology (IT) functions and Facility Management (FM) functions by the telecommunications companies in Uganda has a significant positive relationship with employment generation in Uganda. The qualitative data was analysed using thematic analysis and content analysis, with these findings supporting information revealed through the quantitative analysis. Based on the study’s findings, the researchers recommend that more activities and/or services should be strategically outsourced by companies in the Ugandan telecommunications sector so as to maximize flexibility, and induce innovations and creativity while creating increased employment opportunities in the country.